Reducing blood pressure variability–results from a single-arm proof of concept prospective trial - Eyal Shemesh; Deborah Reynolds; Jasleen Sidhu; Sarah Duncan-Park; Rebecca A. Tejiram; Beth A. Davison; Koji Takagi; Chris Edwards; David Rubinstein; Rachel A. Annunziato; Gad Cotter (Scientific Reports)
Abstract Increased variability in systolic blood pressure, expressed as the coefficient of variation (BPCoV), is associated with poor cardiovascular outcomes. Variability could be due to episodic non-adherence to medical recommendations in some patients. Reports of targeted attempts to mitigate such variation are lacking. A behavioral intervention targeted at patients with initially high BPCoV may decrease variability. In this single-site, single arm prospective proof-of-concept trial, an electronic health record review identified patients with excessive variability (BPCov>10%). Enrolled patients received a blood pressure monitor and a remotely delivered behavioral intervention for 3 months. The primary outcome was mean blood pressure variability before versus after the intervention. Of 551 initially screened patients, 107 (19.4%) met the BPCoV criteria, and 25 consented (6 females and 19 males, mean age 64.24 years). Average BPCoV for the 6 months pre-enrollment was 12.96 (SD=2.11) compared to 7.02 (SD=3.54) during intervention (p<0.001). Other variability metrics also improved. Sensitivity analyses (different timeframes, using measurements obtained in the clinic vs. home monitor) all showed significant improvement. This proof-of-concept trial suggests that patients with high systolic blood pressure variability can successfully engage in a remotely delivered behavioral intervention, and that such an intervention can reduce such variability. Trial Registration: NCT05814562, ClinicalTrials.gov.